Analisis Pantun dalam Manendai Adat Pernikahan di Kecamatan Tapaktuan Kabupaten Aceh Selatan - Fitri Febriani; Razali Razali; Rostina Taib (JIM Pendididikan Bahasa dan Sastra Indonesia, 2020)
This study is entitled Pantun Analysis in Manendai Indigenous Marriage in Tapaktuan Subdistrick, South Aceh Regency. This research problem formulation, namely (1) linguistic structure (rhyme and rhythm) contained in the pantun manendai marriage in the District Tapaktuan, South Aceh District, and (2) the meaning contained in the poem manendai marriage in the District Tapaktuan, South Aceh. This study aims to describe the linguistic structure (rhyme and rhythm) and describe the meaning in poetry in the procession of the customary wedding ceremony in Tapaktuan District, South Aceh Regency. The method used in this study is a qualitative descriptive method with a qualitative approach. The source of the data in this study was the Manendai procession which was carried out in three villages in Tapaktuan Subdistrict, namely Jambo Apha Village, Hulu Village and Hilir Village. Data collection in this study uses the record technique. Data analysis conducted in this research was in the form of qualitative descriptive. The results showed that in the pantun manendai there is (1) a linguistic structure, namely (a) rhyme based on sound includes perfect rhyme, imperfect rhyme, absolute rhyme, open rhyme, closed rhyme and alliteration rhyme, (b) rhyme based on location includes final rhyme, flat rhyme , rhymes are parallel, rhymes hugging, crosses rhyme, rhyme string and rhyme broken, (c) the rhythm produced is the strains of high, low, long, hard, soft, and fast sound; and (2) The meanings contained are denotative meanings and connotative meanings